The significance of intraparticle and interparticle diffusion during CO2 gasification of biomass char in a packed bed. (15th February 2022) - Phounglamcheik, Aekjuthon; Bäckebo, Markus; Robinson, Ryan; Umeki, Kentaro
Graphical abstract: Highlights: Intraparticle and interparticle diffusions interacted and determined gasification rates in packed beds. The apparent rates of monodispersed and polydispersed particles are significantly different. Median size of the particle size distribution (PSD) can predict the intraparticle diffusion effects. The size of smaller fraction in PSD controlled the diffusion through the bed channels. Abstract: This study investigates the influences of intraparticle and interparticle diffusions on the reaction rates of char gasification in a packed bed without forced convective flows. The main objective is to elucidate how the dominant scales of mass diffusion resistance change based on particle size distributions (PSD). CO2 gasification rates were measured by thermogravimetric analyses (TGA) of spruce char produced from pilot-scale reactors. Experimental setups using two TGA devices highlighted the effects on different rate-limiting steps. Effects of intraparticle diffusion were investigated with a single layer of monodispersed particles between 75 µm and 6.3 mm using a commercial TGA. Effects of interparticle diffusion were investigated with a packed bed of monodispersed and polydispersed particles using a macro-TG. At the particle scale, gasification rate decreased with the increase of particle size when the reaction was controlled by intraparticle diffusion. This effect can be described by the effectiveness factor with Thiele modulus. At the bed scale, void fraction and tortuosity of the packed bed are influential parameters on diffusivity of CO2 through the bed channels. Due to its non-sphericity of the char particles, the bed of relatively large particles had high void fraction and the presence of smaller particles were essential to lower the bed void size. Consequently, smaller size fraction in the PSD had a major impact on the diffusion resistance at bed scale. It means that the diffusion resistances at particle and bed scales are sensitive to different size fractions in the PSD. It allows one to tweak the overall reaction rates in packed beds by manipulating the PSD if the dominant mass transport mechanism is diffusion.